2007
DOI: 10.4161/psb.2.2.4073
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Associated Methylobacteria as Co-Evolved Phytosymbionts

Abstract: Due to their wall-associated pectin metabolism, growing plant cells emit significant amounts of the one-carbon alcohol methanol. Pink-pigmented microbes of the genus Methylobacterium that colonize the surfaces of leaves (epiphytes) are capable of growth on this volatile C1-compound as sole source of carbon and energy. In this article the results of experiments with germ-free (gnotobiotic) sporophytes of angiosperms (sunflower, maize) and gametophytes of bryophytes (a moss and two liverwort species) are summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 37 publications
(56 reference statements)
1
90
0
3
Order By: Relevance
“…2). As detailed elsewhere, 4,7,8 and corroborated by Tani et al, 3 M. funariae is a bryophyte-associated prokaryotic microbe that may also inhabit gametophytes of other cryptogamic plants, such as ferns. Based on our studies and those of others 13 it has been concluded that methylobacteria are methanol-consuming phytosymbionts.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…2). As detailed elsewhere, 4,7,8 and corroborated by Tani et al, 3 M. funariae is a bryophyte-associated prokaryotic microbe that may also inhabit gametophytes of other cryptogamic plants, such as ferns. Based on our studies and those of others 13 it has been concluded that methylobacteria are methanol-consuming phytosymbionts.…”
Section: Discussionmentioning
confidence: 82%
“…14 These data, which were generated on greenhousegrown tomato (Lycopersicon esculentum) plants, are difficult to reconcile with the facts that (a) stomata are open during the light period, but closed in the dark, and (b) leaf-associated methylobacteria preferentially occur close to stomatal pores. 8 We conclude that more detailed work on the methylobacterium-gametophyteinteractions are necessary to further explore the postulated "phytosymbionthypothesis" outlined in two articles published in this journal. 4,8 the authors as PPFMs (see ref.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations